Assessment of mobility impairment in patients with multiple sclerosis - Edyta Guty; Magdalena Kozimala; Beata Boratyn; Aneta Mrozowicz; Agata Wojtowicz; Luiza Balicka-Adamik (Kazimierz Wielki University, 2018)
Multiple sclerosis (Lat. sclerosis multiplex, SM) is a chronic inflammatory neurodegenerative disease that affects the central nervous system (CNS). Common symptoms of the SM include mobility impairment, sensory loss (paraesthesia), cerebellar dysfunctions (balance problems), visual disturbances, autonomic dysfunctions and pain syndromes as well as psychiatric disorders (cognitive and emotional disturbances). Aim of work was to assess mobility impairment symptoms among patients with SM in relation to progression of the disease, length of time a patient suffered from it, and influence of the symptoms on functional capacity and self-care management. The study was conducted on a group of 67 patients (74.6% women, 22-74 age range) of Neurology Ward of Medical Care Centre in Jarosław (south-eastern Poland) and its Neurology Clinic who were diagnosed with SM. The study was based on a self-constructed diagnostic questionnaire. The most prevalent (32; 47.8%) type of SM was progressive-relapsing. Balance and coordination impairment (from 1 to 7, average 4.38) were indicated by 74.6% respondents. The incidence of spasticity and problems caused by it were indicated by 31.3%. Mobility dysfunctions were reported by respondents who had the disease longer in comparison to those who did not indicate such impairment (average 10.92 years vs 3.02; p